Amelioration and Pejoration of Arabic Loanwords in Hausa: Evidence of Semantic Change and Implications for Language Teaching (British Journal of Multidisciplinary and Advanced Studies, 2026)
This study investigates semantic change in twenty Arabic loanwords in Hausa, examining how borrowed lexical items undergo meaning elevation (amelioration) and meaning degradation (pejoration) in the host language. The twenty words analysed — eight exemplifying amelioration and twelve exemplifying pejoration — provide concrete linguistic evidence of the processes through which Arabic source meanings are transformed, inverted, narrowed, or entirely replaced during integration into the Hausa lexicon. The study reveals that amelioration in Hausa Arabic loanwords operates primarily through the naming tradition sub-process, by which words carrying neutral, negative, or inanimate referential meanings in Arabic are elevated to honorific human naming functions in Hausa — exemplified by Safinaa (ship to female name), Unaizaa (she-goat to female name), and Mal'uunatu (accursed to female name). Pejoration operates through semantic inversion, register degradation, and taboo transfer, illustrated by shaakira (grateful to sex organ), maulaa (Lord to beg), and tsubbu (medicine to sorcery). The study derives significant implications for language teaching, arguing that awareness of semantic divergence between Arabic source meanings and Hausa borrowed meanings is indispensable for effective bilingual education, Arabic language instruction, and the prevention of pragmatic errors among Hausa learners of Arabic and Arabic learners of Hausa.